A user‐friendly means to scale from the biochemistry of photosynthesis to whole crop canopies and production in time and space – development of Java WIMOVAC. (7th October 2016) - Song, Qingfeng; Chen, Dairui; Long, Stephen P.; Zhu, Xin‐Guang
Abstract: Windows Intuitive Model of Vegetation response to Atmosphere and Climate Change (WIMOVAC) has been used widely as a generic modular mechanistically rich model of plant production. It can predict the responses of leaf and canopy carbon balance, as well as production in different environmental conditions, in particular those relevant to global change. Here, we introduce an open source Java user‐friendly version of WIMOVAC. This software is platform independent and can be easily downloaded to a laptop and used without any prior programming skills. In this article, we describe the structure, equations and user guide and illustrate some potential applications of WIMOVAC. Abstract : Windows Intuitive Model of Vegetation response to Atmosphere and Climate Change (WIMOVAC) has been used widely as a generic mechanistically rich model scaling from biochemistry of leaf photosynthesis to canopy processes and plant production. This paper describes an open‐source JAVA user‐friendly version of WIMOVAC. It is platform independent and can be easily downloaded to a laptop and used without any prior programming skill.